Integrating Experiential Learning into the Merdeka Curriculum for Early Childhood Education in Indonesia - Wahyuningsih, Dian; Küçükoğlü, Adnan (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the integration of experiential learning within the Merdeka Curriculum for early childhood education in Indonesia through a descriptive qualitative method using a systematic literature review of 126 national and international journal articles published between 2017 and 2024. Articles were selected using keyword combinations experiential learning, Merdeka curriculum, and early childhood education from accessible databases such as Google Scholar, Scopus, and DOAJ, and reviewed through four stages: identification, screening, eligibility, and inclusion. The study examines how experiential learning strategies can enhance holistic development in young children by fostering active engagement, critical thinking, creativity, and socio-emotional growth. Findings indicate that experiential learning supports child-centered education when teachers are adequately trained, technology is effectively used, and community involvement is encouraged. However, challenges include inconsistent teacher competencies, lack of infrastructure, and limited policy support. The review emphasizes the need for contextualized teacher training and adaptive education policies. By offering evidence-based insights, this study contributes to best practices and policy recommendations for early childhood education in Indonesia, positioning experiential learning as a transformative approach to prepare a confident, creative, and compassionate generation.